Analgesic and Anesthetic Efficacy of Rocuronium/Sugammadex in Otorhinolaryngologic Surgery: A Propensity Score-Matched Analysis - En-Bo Wu; Chao-Ting Hung; Sheng-Dean Luo; Shao-Chun Wu; Tsung-Yang Lee; Jo-Chi Chin; Peng-Neng Tsai; Johnson Chia-Shen Yang (MDPI AG, 2022)
The use of rocuronium/sugammadex in otorhinolaryngologic surgery improves intubation conditions and surgical rating scales. This study primarily aimed to evaluate the effect of the combination of rocuronium and sugammadex on intraoperative anesthetic consumption. The secondary outcomes were the intraoperative and postoperative morphine milligram equivalent (MME) consumption, duration of intraoperative hypertension, extubation time, incidence of delayed extubation and postoperative nausea and vomiting, pain score, and length of stay. A total of 2848 patients underwent otorhinolaryngologic surgery at a tertiary medical center in southern Taiwan. After applying the exclusion criteria, 2648 of these cases were included, with 167 and 2481 in the rocuronium/sugammadex and cisatracurium/neostigmine groups, respectively. To reduce potential bias, 119 patients in each group were matched by propensity scores for sex, age, body weight, and type of surgery. We found that the rocuronium/sugammadex group was associated with significant preservation of the intraoperative sevoflurane and MME consumption, with reductions of 14.2% (p = 0.009) and 11.8% (p = 0.035), respectively. The use of the combination of rocuronium and sugammadex also significantly increased the dose of intraoperative labetalol (p = 0.002), although there was no significant difference in intraoperative hypertensive events between both groups. In conclusion, our results may encourage the use of the combination of rocuronium and sugammadex as part of volatile-sparing and opioid-sparing anesthesia in otorhinolaryngologic surgery.